1994
DOI: 10.2134/jpa1994.0448
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen and Fungicide Effects on Yield Components and Disease Severity in Wheat

Abstract: Spring N applications increase wheat (Triticum aestivum L.) grain yields in the Mid‐South. The interactive effect of increased N rates and foliar fungicide applications on the common Mid‐South winter wheat foliar diseases—leaf blotch (Septoria tritici Rob. in Desm.), glume blotch and leaf spot [S. nodorum (Berk.) Berk.], and leaf rust (Puccinia recondita Rob. ex Desm. f. sp. tritici)—is not clearly understood. Research was initiated in 1984 on a Collins silt loam soil (coarse‐silty, mixed, acid, thermic Aquic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
3
6

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 7 publications
4
31
3
6
Order By: Relevance
“…This result contrasted with similar comparisons in the literature; several have reported high concentrations of N in the canopy favored leaf rust (Walters and Bingham, 2007), powdery mildew (Olesen et al, 2003a), and septoria (Howard et al, 1994; Lovell et al, Table 10. UTC, untreated check no fungicide; T3, fungicide at Zadoks Growth Stage (GS) 65; T123, fungicide at approximately GS 30, GS 39, and GS 65.…”
Section: ---------------------------% Severity † --------------------contrasting
confidence: 75%
“…This result contrasted with similar comparisons in the literature; several have reported high concentrations of N in the canopy favored leaf rust (Walters and Bingham, 2007), powdery mildew (Olesen et al, 2003a), and septoria (Howard et al, 1994; Lovell et al, Table 10. UTC, untreated check no fungicide; T3, fungicide at Zadoks Growth Stage (GS) 65; T123, fungicide at approximately GS 30, GS 39, and GS 65.…”
Section: ---------------------------% Severity † --------------------contrasting
confidence: 75%
“…Rice blast (Kürschner et al 1992;Long et al 2000) is the best-known example of such a disease. Among wheat diseases, powdery mildew (Last 1953;Teich et al 1987), leaf rust (Howard et al 1994;Teich et al 1987), stripe rust or yellow rust (Ash and Brown 1991;Danial and Parlevliet 1995) and several other diseases (Howard et al 1994) have been reported to increase in severity as the rate of nitrogen application is increased. Transcription analyses show that sugar and inorganic nitrogen act as both metabolites and signaling molecules.…”
Section: Effect Of Abiotic Stress On Carbohydrate Content and Resistamentioning
confidence: 99%
“…Management practices such as N fertilization can also affect the expression of wheat foliar diseases [82,84] and the effectiveness of foliar fungicide application [72,82,84,85]. Increasing N rates may cause negative, positive or neutral effect on foliar disease severity, depending on the geographic location [86] and the type of disease.…”
Section: The Use Of Fungicides In the Integrated Foliar Disease Managmentioning
confidence: 99%
“…Increasing N rates may cause negative, positive or neutral effect on foliar disease severity, depending on the geographic location [86] and the type of disease. The magnitude and direction of the influence of N supply on Septoria leaf blotch severity has been studied with contrasting results [85,87,88,89]. Simón et al [82,84,90] found that in conducive conditions, N fertilization increases the severity of Septoria leaf blotch and discussed the effect of different factors affecting the influence of N supply.…”
Section: The Use Of Fungicides In the Integrated Foliar Disease Managmentioning
confidence: 99%
See 1 more Smart Citation